The downfall of Turkish–Israeli relations: a cold peace between former strategic allies - Uzer, Umut (Informa UK Limited, 2020)
The entire edifice of the strategic Turkish-Israeli alliance of the 1990s collapsed during the last ten years, with relations between the former partners characterised by antagonism and total lack ...